STRATEGI PENGENTASAN KEMISKINAN MELALUI PROGRAM PENDIRIAN DAN PENGEMBANGAN KOPERASI - Endang Rusdianti; Sri Purwantini; Nirsetyo Wahdi (Jurnal Dinamika Sosial Budaya, 2019)
The results of the first year of research show that there has been a group of business activities called UPPKS (Usaha Peningkatan Pendapatan Keluarga Sejahtera) but the results are less than optimal because there are still many obstacles and weaknesses in managing management and business activities. The existing activities turned out to be still individual, not in groups. The research objective is the development of sustainable business activity groups in the form of cooperative embryos related to efforts to increase the role of women for poverty alleviation.This research uses a qualitative method which is a description of conditions in the field. The solution implemented is through training and assistance in establishing cooperatives.The results obtained are increased motivation to develop business through group activities, namely cooperatives, this is evident from the willingness to establish cooperatives even though they are not in the form of legal entities (embryos). Training and assistance are needed for the continuity of the cooperative.